2021
DOI: 10.1016/j.annonc.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

FAST: a randomised phase II study of zolbetuximab (IMAB362) plus EOX versus EOX alone for first-line treatment of advanced CLDN18.2-positive gastric and gastro-oesophageal adenocarcinoma

Abstract: Background: Claudin 18.2 (CLDN18.2) is contained within normal gastric mucosa epithelial tight junctions; upon malignant transformation, CLDN18.2 epitopes become exposed. Zolbetuximab, a chimeric monoclonal antibody, mediates specific killing of CLDN18.2-positive cells through immune effector mechanisms. Patients and methods: The FAST study enrolled advanced gastric/gastro-oesophageal junction and oesophageal adenocarcinoma patients (aged 18 years) with moderate-to-strong CLDN18.2 expression in 40% tumour cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
263
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(270 citation statements)
references
References 21 publications
3
263
0
4
Order By: Relevance
“…Lenvatinib targets and inhibits vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF) tyrosine kinase receptors. Preclinical trials demonstrated lenvatinib's ability to function as an antitumor treatment against varying solid tumor types [32]. It is believed that the tumor microenvironment is a critical point at which resistance to checkpoint inhibition occurs [32].…”
Section: Combination With Lenvatinibmentioning
confidence: 99%
See 2 more Smart Citations
“…Lenvatinib targets and inhibits vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF) tyrosine kinase receptors. Preclinical trials demonstrated lenvatinib's ability to function as an antitumor treatment against varying solid tumor types [32]. It is believed that the tumor microenvironment is a critical point at which resistance to checkpoint inhibition occurs [32].…”
Section: Combination With Lenvatinibmentioning
confidence: 99%
“…Preclinical trials demonstrated lenvatinib's ability to function as an antitumor treatment against varying solid tumor types [32]. It is believed that the tumor microenvironment is a critical point at which resistance to checkpoint inhibition occurs [32]. Evidence suggests intervening treatment can modify this environment, and that the tumor microenvironment can predict the response to a checkpoint blockade [32].…”
Section: Combination With Lenvatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a recent exome, transcriptome, immune profile analysis identified multiple independent prognostic factors in EGC discriminating longer from shorter survivors. 95 96 This agent is currently being evaluated in two phase 3 trials (NCT03504397, NCT03653507).…”
Section: Future Directionsmentioning
confidence: 99%
“…In der vorliegenden, randomisierten Phase II Studie FAST wurde die Sicherheit und Effektivität von Zolbetuximab (Erstgabe 800 mg/m 2 gefolgt von 600 mg/m 2 jeweils an Tag 1 jedes Zyklus) in Kombination mit einer Chemotherapie nach dem EOX* Schema (Epirubicin, Oxaliplatin, Capecitabin für max. 8 Zyklen) vs. der Chemotherapie alleine untersucht [3]. Ein dritter explorativer Arm untersuchte die Kombination aus einer höheren Zolbetuximab Dosis (1000 mg/m 2 ) mit Chemotherapie.…”
Section: Transfer In Die Praxis Von Pd Dr Med Georg Martin Haag (Heidelberg)unclassified